Pixação e o circuito artístico brasileiro (2005-2021): disputas e novas possibilidades. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The present research presents the phenomenon of absorption and interaction/integration of pixação in the Brazilian artistic circuit, especially in São Paulo, from the event of occupation of the Sao Paulo International Art Biennial by pixadores, which took place in 2008. In this broad context, there are ruptures in the uses and functions of the practice of pixação, along with the context of these actions and others that extend with the introduction of digital media and the expansion of the artistic market. In this sphere, it aims to question visual expressions and their discourses, considering what changes and/or continuities of expression and discourse occur when their production started to be inserted in unusual places. In other words, it is proposed to analyze the paradigm break, when one observes the expansion of the circulation and acceptance of pixação, which was traditionally performed in public spaces and which is now assimilated by established events in the artistic field, such as, for example, the São Paulo International Art Biennial and the specialized galleries. In addition to these questions, the research also investigates how part of the (digital) media influence and collaborate for the dissemination and expansion of the work developed by pixadores and the formation of their social networks. To achieve the proposed objectives, the development of the research has reflections and theoretical links on the history of art, questions about the identity of pixadores, aesthetic expression, spaces of power, right to/of the city, symbolic field and its different temporalities, dealing with from a documental analysis of several sources such as printed newspapers, digital media and posters. Néstor García Canclini, Anne Cauquelin, Armando Silva, Michel de Certeau and Maria Lúcia Bastos Kern were used as main theoretical references to analyze the relationship between art and the city, Latin American cultural complexity and the concept of hybridity in art.
Keywords: Pixação; Pichação; Circuito Artístico; Arte Contemporânea; Cultura Visual; Pixação; Graffiti; Artistic Field; Contemporary art; CNPQ::CIENCIAS HUMANAS::HISTORIA